2005
DOI: 10.1086/497396
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Halo Substructure with Giant Stars: The Velocity Dispersion Profiles of the Ursa Minor and Draco Dwarf Spheroidal Galaxies at Large Angular Separations

Abstract: We analyze velocity dispersion profiles for the Draco and Ursa Minor (UMi) dwarf spheroidal (dSph) galaxies based on published and new Keck HIRES spectra for stars in the outer UMi field. Washington+DDO51 filter photometric catalogs provide additional leverage on membership of individual stars, and beyond 0.5 King limiting radii (r lim ) identify bona fide dSph members up to 4.5 times more efficiently than simple color-magnitude diagram selections. Previously reported "cold populations" at r lim are not obviou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
138
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(156 citation statements)
references
References 33 publications
17
138
1
Order By: Relevance
“…3a and 3b): very few RVoutliers are found among our Carina giant candidates overall, and, in addition, the small number of giant candidates we find that do not share the Carina dSph RV lie predominantly in the 332 km s À1 group. Furthermore, Figure 5b suggests that the outer halo is highly substructured (at least when traced by giant stars), a result that is also evident from Figure 2 in Muñoz et al (2005). In such circumstances, to obtain substantial contamination in our survey would require a considerably unfortunate conspiracy of phenomena to produce a second halo substructure with the same RV, approximate distance, and CMD distribution as Carina; we consider this possibility unlikely.…”
Section: Implications Of Widely Separated Rv Membersmentioning
confidence: 74%
See 2 more Smart Citations
“…3a and 3b): very few RVoutliers are found among our Carina giant candidates overall, and, in addition, the small number of giant candidates we find that do not share the Carina dSph RV lie predominantly in the 332 km s À1 group. Furthermore, Figure 5b suggests that the outer halo is highly substructured (at least when traced by giant stars), a result that is also evident from Figure 2 in Muñoz et al (2005). In such circumstances, to obtain substantial contamination in our survey would require a considerably unfortunate conspiracy of phenomena to produce a second halo substructure with the same RV, approximate distance, and CMD distribution as Carina; we consider this possibility unlikely.…”
Section: Implications Of Widely Separated Rv Membersmentioning
confidence: 74%
“…Such flat profiles over a comparable structural radial range have now been reported (although not to the radial extent of this study) for several dSph's: Sculptor ( Majewski et al 2006, in preparation). Note that while Wilkinson et al (2004) found a sudden drop in velocity dispersion at about r lim for both Ursa Minor and Draco, this feature could not be reproduced by Muñoz et al (2005) when reanalyzing these profiles when Washington+DDO51 photometric and additional spectroscopic data were used to check them. Kleyna et al (2004) have also found Sextans to have a predominantly flat profile but with a cold velocity dispersion at about r lim (and a kinematically cold center as well); given that similar claims for cold points near r lim in the Ursa Minor and Draco dSph's have not held up under further scrutiny, the Sextans result warrants further investigation.…”
Section: Velocity Dispersion Trend Of Carina Starsmentioning
confidence: 97%
See 1 more Smart Citation
“…The radial velocity dispersion profile is a powerful tool for investigating multi-component self-gravitating systems, since it is sensitive to the dark matter distribution and accessible to observations (e.g., Pasetto et al 2010). Recently, radial velocity data have become available to track the line-of-sight velocity dispersion as a function of radius for many LG dwarf galaxies (e.g., Pasetto et al 2010;Tolstoy et al 2004;Westfall et al 2006;Wilkinson et al 2004;Muñoz et al 2005;Walker et al 2006aWalker et al ,b, 2009Sohn et al 2007; Koch et al 2007c,b;Muñoz et al 2006), and these data A&A 525, A99 (2011) permit more detailed modelling of the dwarf galaxies kinematic status (e.g., Kroupa 1997;Kleyna et al 1999;Kazantzidis et al 2004;Read et al 2006;Peñarrubia et al 2008Peñarrubia et al , 2009Pasetto et al 2010). For the same approach to multi-component dSphs in the cosmological ΛCMD contest see, Stoehr et al (2002) and Hayashi et al (2003) or, in a purely dynamical collisonless regime see Ciotti & Morganti (2009), where the primordial stellar population is embedded in an extended dark matter halo without considering any gas process.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also alternative explanations (e.g., Muñoz et al 2005;Sohn et al 2077) favoring tidal disruption and low mass-to-light ratios. In the case of the distant Galactic dSph satellite Leo II curious stellar overdensities have been found at larger distances whose nature is not yet understood (Komiyama et al 2007;Coleman et al 2007), and the nearby dSph Ursa Minor may experience tidal disruption as indicated by its elongated, S-shaped stellar density distribution (e.g., Palma et al 2003).…”
Section: Radial Velocity Measurements Across the Full Angular Extent mentioning
confidence: 99%